2019
DOI: 10.1097/sle.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laparoscopic Sleeve Gastrectomy on Nonalcoholic Fatty Liver Disease

Abstract: Obesity is associated with nonalcoholic fatty liver disease which is one of the most common causes of chronic liver disease. FibroScan is a noninvasive tool for liver stiffness measurement and controlled attenuation parameter to evaluate liver steatosis and fibrosis. We aimed to demonstrate the effect of laparoscopic sleeve gastrectomy on liver steatosis and fibrosis. Of the 120 consecutive patients screened, 72 were enrolled in this study. FibroScan M probe and XL probe were used for the evaluation of liver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Nonalkolik steatohepatit is the most common chronic liver disease, with a prevalence rate of up to 90% in morbidly obese people. It can progress to liver fibrosis and even cirrhosis [7, 18, 19]. Liver biopsy is the gold standard technique in the diagnosis of hepatosteatosis; however, it is an invasive method [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonalkolik steatohepatit is the most common chronic liver disease, with a prevalence rate of up to 90% in morbidly obese people. It can progress to liver fibrosis and even cirrhosis [7, 18, 19]. Liver biopsy is the gold standard technique in the diagnosis of hepatosteatosis; however, it is an invasive method [20].…”
Section: Discussionmentioning
confidence: 99%
“…LSG is the most common bariatric procedure around the world [21][22][23]. Improvement of hepatosteatosis has been reported with a decrease in BMI after LSG [6,7,24]. Esquivel et al [25] showed that all the participating patients reversed or reduced the stage of hepatosteatosis 1 year after LSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 1,462 articles were excluded based on study title and abstract, 136 articles were selected for full text review, of which 31 articles met the final inclusion criteria (Figure 2). In total, five articles originated from the United States (36)(37)(38)(39)(40), six from Brazil (41)(42)(43)(44)(45)(46), four from France (18,(47)(48)(49), two from Poland (50,51), Australia (52,53) and Japan (54,55) respectively and one each from Denmark (56), Canada (57), Germany (58), Greece (59), India (60), Israel (61), Netherlands (62), Saudi Arabia (63), Taiwan (64) and Turkey (65). Of the 31 included articles, there were 20 single-arm and 11 doublearm studies.…”
Section: Summary Of Included Articlesmentioning
confidence: 99%